2010
DOI: 10.1016/s1569-18611170007-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Horticultural Activity Programme for Persons with Psychiatric Illness

Abstract: To investigate the effect of applying horticulture activity on stress, work performance and quality of life in persons with psychiatric illness. Methods: This study was a single-blinded randomized controlled trial. Using convenience sampling, 24 participants with psychiatric illness were recruited to participate in a horticultural programme and were randomly assigned to experimental and control groups. Two participants dropped out from experimental groups after assignment. Ten participants in the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 21 publications
0
28
1
2
Order By: Relevance
“…Second, the quantitative results from the questionnaire showed that subjects did not have a significant reduction in stress or anxiety, and this is consistent with the observational ratings of affect. This is, however, inconsistent with our pilot study [8] and many other studies of HT [39,42], as well as the perceptions of focus group participants who said that they experienced relief of stress and anxiety. The insignificant change in stress and anxiety could be explained by a flooring effect of the stress and anxiety scores at pre-test.…”
Section: Outcomes and Processes Of Horticultural Therapycontrasting
confidence: 99%
See 2 more Smart Citations
“…Second, the quantitative results from the questionnaire showed that subjects did not have a significant reduction in stress or anxiety, and this is consistent with the observational ratings of affect. This is, however, inconsistent with our pilot study [8] and many other studies of HT [39,42], as well as the perceptions of focus group participants who said that they experienced relief of stress and anxiety. The insignificant change in stress and anxiety could be explained by a flooring effect of the stress and anxiety scores at pre-test.…”
Section: Outcomes and Processes Of Horticultural Therapycontrasting
confidence: 99%
“…People's interactions with plants, through goal-orientated horticultural activities in the form of active gardening, as well as the passive appreciation of nature, could be therapeutic to people with mental disorders in many ways [5,6]. First, horticulture could have emotional benefits, such as reducing stress, reducing psychiatric symptoms, stabilizing mood, and increasing the sense of tranquility, spirituality, and enjoyment [1,[7][8][9][10]. Second, it could help people to reduce fatigue and restore attention and cognitive ability [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gardening activity is based not only on the effects of a series of the gardening activity of growing, harvesting and incorporating them into life but also on the effect of the physical function being restored as well as the attachment to the plant (Hayashi et al, 2008;Gonzalez et al, 2010;Hansen-Ketchum et al, 2009;Maller et al, 2006;Page, 2008;Haller et al, 2019;Rappe, 2005). Additionally, the gardening activity is thought to have psychological improvement effects such as gaining self-confidence, sense of achievement, satisfaction, joy, and happiness, as well as relieving stress (Sempik et al, 2003;Ulrich et al, 1991); Although many studies have been conducted using the gardening activity with the children, adults, elderly, people with disabilities and ailing patient (Cimprich, 1993;Relf & Dorn, 1995;Simon & Straus, 1998;Cimprich & Ronis, 2003;Kam & Siu, 2010;Gonzalez et al, 2010;Kim et al, 2012;Kotozaki, 2014). Waliczek et al reported that children's gardening activities could help children's self-esteem and stress reduction (Waliczek et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…์ด๋Ÿฐ ์›์˜ˆํ™œ๋™์€ ์ •์‹ ์ ์ธ ์ŠคํŠธ๋ ˆ์Šค๋ฅผ ๊ฐ์†Œ์‹œํ‚ค๊ณ , ๊ฐ์ •์ •์ธ ์•ˆ์ •๊ฐ์„ ์ฃผ๊ณ , ์ธ์ง€ ๊ธฐ๋Šฅ์— ๋„์›€์ด ๋œ๋‹ค๋Š” ๊ฒƒ์€ ์•Œ๋ ค์ ธ ์žˆ๋‹ค (Pfeffer et al, 2009). ์ด๋ฅผ ๋ฐ”ํƒ•์œผ๋กœ ์›์˜ˆ์น˜ ๋ฃŒ๋„ ์‹œํ–‰์ด ๋˜๋Š”๋ฐ ์šฐ์šธ์ฆ ํ™˜์ž๋‚˜ ๋‡Œ์กธ์ค‘ ํ™˜์ž์— ๋„์›€์ด ๋˜๊ณ , ํ•™์ƒ์ด๋‚˜ ๊ต์‚ฌ๋“ค์—๊ฒŒ๋„ ์ •์„œ์  ์•ˆ์ • ๋“ฑ์— ๋„์›€์„ ์ฃผ๋Š” ๊ฒƒ์œผ๋กœ ์•Œ๋ ค์ ธ ์žˆ๋‹ค (Barnicle and Midden, 2003;Kam and Siu, 2010;Kamioka et al, 2014). ์ด๋Ÿฐ ์›์˜ˆํ™œ๋™์€ ๊ฑด๋ฌผ ์— ๊ฐ‡ํžŒ ํ™˜๊ฒฝ์—์„œ ์žฅ์‹œ๊ฐ„ ์ผํ•˜๋Š” ๊ทผ๋กœ์ž์—๊ฒŒ๋Š” ์ž์—ฐ๊ณผ ์ ‘ํ•  ์ˆ˜ ์žˆ๋Š” ํ™˜๊ฒฝ์„ ์ œ๊ณตํ•ด ์ฃผ๊ณ , ์ง๋ฌด์ŠคํŠธ๋ ˆ์Šค๋ฅผ ๋‚ฎ์ถ˜๋‹ค(Lee and Lee, 2016).…”
unclassified